Lactococcus garvieae, an unusual pathogen in infective endocarditis: case report and review of the literature (2019)
Lactococcus garvieae is an unusual cause of infective endocarditis (IE). No current diagnostic and therapeutic guidelines are available to treat IE caused by these organisms. Based on a case report, we provide a review of the literature of IE caused by L. garvieae and highlight diagnostic and treatment challenges of these infections and implications for management. A 50-year-old Asian male with mitral prosthetic valve presented to the hospital with intracranial haemorrhage, which was successfully treated. Three weeks later, he complained of generalized malaise. Further work up revealed blood cultures positive for Gram-positive cocci identified as L. garvieae by MALDI-TOF. An echocardiogram confirmed the diagnosis of IE. Susceptibility testing showed resistance only to clindamycin. Vancomycin plus gentamicin were started as empirical therapy and, subsequently, the combination of ceftriaxone plus gentamicin was used after susceptibility studies were available. After two weeks of combination therapy, ceftriaxone was continued as monotherapy for six additional weeks with good outcome. Twenty-five cases of IE by Lactococcus garvieae have been reported in the literature. Compared to other Gram-positive cocci, L. garvieae affects more frequently patients with prosthetic valves. IE presents in a subacute manner and the case fatality rate can be as high as 16%, comparable to that of streptococcal IE (15.7%). Reliable methods for identification of L. garvieae include MALDI-TOF, 16S RNA PCR, API 32 strep kit and BD Automated Phoenix System. Recommended antimicrobials for L. garvieae IE are ampicillin, amoxicillin, ceftriaxone or vancomycin in monotherapy or in combination with gentamicin.